Development of Well-Aligned TiO2 Nanotube Arrays to Improve Electron Transport in Dye-Sensitized Solar Cells - Kyung-Ho Chung; Md. Mahbubur Rahman; Hyun-Seok Son; Jae-Joon Lee (International Journal of Photoenergy)
We fabricated well-aligned one-dimensional (1-D) titania nanotubes (TNT) on transparent conducting oxide (TCO) by anodization of Ti foil. Different lengths of TNTs were prepared by varying the applied potential (70 V) time, and we investigated the performance of these TNTs in dye-sensitized solar cells (DSSCs), transplanted onto a 6 μm TNP adhesion layer. The fabricated TNTs arrays (length 15 μm) photoelectrode showed 24% increased efficiency compared to the TNP photoelectrode of 17 μm thickness. We further investigated the performances of DSSCs for the TNTs (1 wt%) incorporated TNP photoelectrode and obtained 22% increased efficiency. The increased efficiency of the pure TNTs arrays and TNT-mixed TNP photoelectrodes was attributed to the directional electron movement of TNTs and light scattering effect of the TNT with the decreased rate of back electron transfer. The anodized and fabricated TNTs and DSSCs were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM), and electrochemical impedance spectroscopy (EIS).